DocuDesk: An Interactive Surface for Creating and Rehydrating Many-to-Many Linkages among Paper and Digital Documents - Everitt, Katherine; Morris, Meredith Ringel; Brush, A.J.; Wilson, Andy (3rd IEEE International Workshop on Horizontal Interactive Human Computer Systems, 2008. TABLETOP 2008., 2008)
Knowledge workers often undertake tasks that involve a variety of information artifacts, including both paper and digital documents. In this paper, we first summarize findings from a study that illustrate some of the challenges of managing tasks that include both paper and digital content. We then introduce DocuDesk, a prototype interactive desk that demonstrates interaction techniques for establishing many-to-many linkages among paper and digital documents which can be used to quickly “rehydrate” task state.